Application of Anti-Corruption Educational Values ​​at Madrasah Ibtidaiyah Assa'adah - Siti Rohmah Adawiyah (Edumaspul: Jurnal Pendidikan, 2022)
Education is the beginning of the formation of a person to be better, with education a person can shape himself away from despicable things, such as acts of corruption. Corruption is the act of someone who abuses trust in an issue or organization to take advantage. Corruption is a crime that is detrimental to state finances. The role of the teacher is very important for students to provide an understanding of what acts of corruption are and also play a role in instilling honesty values ​​in students, so that students can take honest actions and not commit lies or acts of corruption. Anti-corruption education in schools is very important and must be implemented properly because the application of anti-corruption education must start from school education. Therefore, this research was carried out with the aim of knowing the anti-corruption education applied at Madrasah Ibtidaiyah Asa'adah. The research method in this study uses literature study and observation. The technique of collecting data is by interviewing. The results of research conducted by Madrasah Ibtidaiyah apply the value of anti-corruption education through subjects, including: morals and PKN. In this way, Madrasah Ibtidaiyah Assa' is able to familiarize students with good behavior from an early age through the education provided by the school.